1995
DOI: 10.1046/j.1471-4159.1995.65010275.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Role of N‐Acetylaspartate in Cerebral Osmoregulation

Abstract: Marked abnormalities of the magnetic resonance intensity of N‐acetylaspartate (NAA) have been reported in patients with various neurological disorders, but the neurochemical consequences of these alterations are difficult to assess because the function of NAA remains speculative. The purpose of this study was to examine whether NAA plays a role in protecting neurons against osmotic stress. Intracerebral microdialysis was used to expose a small region of the rat dorsolateral striatum to an increasingly hyposmot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
2
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 42 publications
6
73
2
1
Order By: Relevance
“…In the 1990's, Taylor and colleagues proposed that NAA acted as a neuronal osmolyte involved in either neuronal volume regulation, or acid-base homeostasis. (Taylor et al, 1994) Using microdialysis, they demonstrated that NAA concentrations in the extracellular fluid increased in response to hypoosmotic stress (Taylor et al, 1995). Despite this, the changes in extracellular NAA concentrations were relatively modest (from ~14 μM to ~32 μM) as compared with the substantially larger increases in extracellular taurine concentrations (from ~ 12 μM to ~ 80 μM) under the same hypoosmotic conditions.…”
Section: Naa and Osmoregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1990's, Taylor and colleagues proposed that NAA acted as a neuronal osmolyte involved in either neuronal volume regulation, or acid-base homeostasis. (Taylor et al, 1994) Using microdialysis, they demonstrated that NAA concentrations in the extracellular fluid increased in response to hypoosmotic stress (Taylor et al, 1995). Despite this, the changes in extracellular NAA concentrations were relatively modest (from ~14 μM to ~32 μM) as compared with the substantially larger increases in extracellular taurine concentrations (from ~ 12 μM to ~ 80 μM) under the same hypoosmotic conditions.…”
Section: Naa and Osmoregulationmentioning
confidence: 99%
“…First, these investigators observed much larger changes in NAA in response to hypo-osmotic stress than were seen with taurine. Microdialysis studies have shown that taurine concentrations respond more to osmotic changes than have been observed with NAA (Taylor et al, 1995). Second, such large decreases in NAA levels after hypo-osmotic stress have not been observed using other methods (Verbalis, 2006).…”
Section: 31mentioning
confidence: 99%
“…NAA has been shown to be closely related to mitochondrial activity in ATP production and O 2 consumption (6), which suggests an association between [NAA] and metabolic efficiency in the brain (73). Previous studies have shown that [NAA] is associated with both intellectual and neuropsychological (84) measures of cognition in young adults.…”
Section: Effects Of Nitrate Supplementation On Brain Metabolite Concementioning
confidence: 99%
“…1 Despite its high cerebral concentration, however, the functional role of NAA is not yet established beyond doubt, although some studies suggest that NAA could play a role in osmoregulation 2 or as an intermediate for the synthesis of proteins and lipids. 3 As its synthesis and degradation take place in different compartments, it has been suggested that NAA might play a role in the neuronal-glial cell-specific signaling and communication in the development of normal central nervous system.…”
Section: Introductionmentioning
confidence: 99%